Tolerance of Traditional Tidal Swamp Rice to Sheath Bligh (Rhizoctonia solani) - Bambang Prayudi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2000)
The study was conducted to find out some factors affecting low disease intensity and slow diseased development on several traditional rice through i.e. a) regeneration ability afterwards pathogen invation, b) to drive on sclerotium formation on traditional rice straw (i.e. Bayar pahit. Bayar palas. Karang dukuh, Lemo. Pandak) and improve variety (IR 36) in the moisture chamber, and also in water agar + rice sheath extract, c) the difference of internode and sheath long. The result revealed that some traditional rice (Bayar pahit, Bayar palas, Karang dukuh, Lemo and Pandak) possesa good regeneration ability afterward rice hills damaged by a pathogen invation. Pathogen also faided to produce sclerotium on Bayar pahit, Bayar palas, Karang dukuh and Lemo, and it was more due to the lack of available nutrition for pathogen fisiological prosses in the several traditional varieties. It was also possibly has inhibitor chemical compounds that inhibit sclerotium formation. There was known that stem internode was longer than sheath. So the pathogen could not reach to uppers heath. Diseased development was really slow on the traditional varieties that had three characteristics mentioned above.   Key word: Rice, Sheath blight, Tidal swamp